Strategi Guru dalam Meningkatkan Kemampuan Berfikir Kritis Siswa - Widiastuti, Sapona; Surachman, Anista Ika (Journal of Elementary Education Research, 2023)
This research aims to find out how teachers' strategies improve critical thinking skills. The benefit of critical thinking skills from this research is that it can develop the knowledge researched from a theoretical perspective, especially regarding the critical thinking skills of class IV, V, VI students at MI Tarbiyatus Salam Mojoagung. For students, it is useful for increasing motivation and learning achievement. For teachers, it is useful to develop the quality of learning to be better. For institutions, these theoretical benefits are useful as a reference for improving school policies. Meanwhile, the practical benefits of this research are expected to provide benefits to educational practitioners. For students, it is useful to improve students' understanding of several subjects. For teachers, it is useful to increase teacher professionalism in carrying out teaching and learning activities. And for institutions, it is useful as an effort to improve the quality of teaching management. This type of research is field research with a qualitative approach. This research was carried out at MI Tarbiyatus Salam. in June-July 2022 the primary data source is class IV, V, VI teachers while the secondary data source is the teacher structure vision and mission. Data collection techniques use interviews, documentation and observation. After the data is collected, data analysis is carried out using data triangulation techniques from Milles and Hubberman or by looking for supporting data for the research objectives formulated by Data Reduction, Data Presentation, Conclusion Drawing and Verification, and Data Validity. The results of the data reduction are presented in the form of data displays using narrative descriptions. The conclusion of this research is that teacher strategies in improving critical thinking skills are very important for MI Tarbiyatus Salam students so they can develop brilliant ideas so that 4 teacher strategies are needed including: (1) Planning learning activities (2) implementing learning activities (3) evaluation in improving students' critical thinking abilities (4) Supporting and inhibiting factors in improving students' critical thinking abilities at MI Tarbiyatus Salam. There are several supporting factors including teacher enthusiasm in carrying out their duties, adequate facilities. Inhibiting factors include students feeling bored during learning, students not being active in teaching and learning activities, the sentences in the books are very difficult so they can hinder critical thinking abilities.